IMAGING DIAGNOSIS —ANTEMORTEM DETECTION OF OLIGODENDROGLIOMA "CEREBROSPINAL FLUID DROP METASTASES" IN A DOG BY SERIAL MAGNETIC RESONANCE IMAGING. Issue 4 (7th February 2017) - Vigeral, Mariana; Bentley, R. Timothy; Rancilio, Nicholas J.; Miller, Margaret A.; Heng, Hock Gan
Abstract: An English Bulldog underwent radiation therapy of an intracranial, left lateral ventricle mass. Following resolution of the primary mass, an intraventricular fourth ventricle lesion developed. Subsequently, multiple lesions developed from the cervical central canal and leptomeninges. Serial magnetic resonance imaging documented the propagation of lesions along the cerebrospinal fluid (CSF) pathways, known as "CSF drop metastasis." Histopathology confirmed multifocal intraventricular and leptomeningeal oligodendroglioma. Oligodendroglioma should be included in the differential diagnosis for an intraventricular tumor exhibiting apparent CSF drop metastasis.